New Fungal Strains from Peat Soil in Malaysia: Morphological and Molecular Characteristics - Efaq Ali Noman, Efaq Ali Noman; Adel Ali Al-Gheethi c, Adel Ali Al-Gheethi c; Baliks A. Talip, Baliks A. Talip; Radin Mohamed, Radin Maya Saphira; Reyad Almoheer, Reyad Almoheer; Fairoz Ali Al-Wrafy, Fairoz Ali Al-Wrafy; Najeeb Al-Shorgani, Najeeb Al-Shorgani; Hesham Ali El Enshasy, Hesham Ali El Enshasy (Mdpi, 2023)
Fungi have unique properties and are used in many areas of agriculture and industry because they can produce different enzymes. This study aims to study the fungal diversity in peat soil from Pontian in Johor, Malaysia. The fungal isolates were described on different culture media and on a new culture medium called EVA medium and were identified using the phenotypical characteristics and molecular properties of the D1/D2 domain of the 28S large subunit ribosomal RNA (28S rRNA) and ITS (ITS1-ITS4) rDNA regions. The results revealed that 14 fungal species (15 isolates) were identified, among them, 6 were categorized as newly isolated strains and recorded in Malaysia; these include Aspergillus arenarioides EAN603, A. iizukae EAN605, Paraconiothyrium brasiliense EAN202, Parengyodontium album EAN602, Penicillium pedernalense EAN604, and Purpureocillium lilacinum EAN601. The cultural, morphological, microstructure, and molecular characteristics of these new strains have been described in this study. It was noted that the EVA medium exhibited a moderate support for fungal growth and sporulation compared to other culture media. Furthermore, the efficiency of the new medium as an enrichment medium to isolate fungi from peat soils with high ligninolytic content was discussed.